2016
DOI: 10.1088/1757-899x/160/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness of woven kenaf fibre reinforced composites

Abstract: Abstract. This paper presents the role of fibre orientations on the woven-type kenaf fibre reinforced composites. According to literature survey, lack of information regarding to the fracture toughness of woven kenaf fibre reinforced composites. Fracture toughness tests were performed using ASTM D5045. Four fibre orientations were used such as 0/15/0/-15/0, 0/30/0/-30/0, 0/45/0/-45/0 and 0/90/0/-90/0 and on the other hand virgin polyester and unidirectional fibre reinforced composites were also used for compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…This might be due to the cracking of material that happened together with limited plastic deformation. Similar trend was also reported by previous researchers [9], [10]. Table 1 shows KQ (trial KIC) result obtain for both type of hybrid composites material used in this study.…”
Section: A Single Edge Notch Bend Propertiessupporting
confidence: 88%
“…This might be due to the cracking of material that happened together with limited plastic deformation. Similar trend was also reported by previous researchers [9], [10]. Table 1 shows KQ (trial KIC) result obtain for both type of hybrid composites material used in this study.…”
Section: A Single Edge Notch Bend Propertiessupporting
confidence: 88%
“…Ismail et al, [11][12][13][14] used kenaf fiber in the woven form to fabricate composite tubes and plates. Impact strength, fatigue and tensile performances are investigated where the relationship between fiber orientations and number of layers with mechanical performances are the subject of interest.…”
Section: Introductionmentioning
confidence: 99%

Crushing Performances of Kenaf Fibre Reinforce Composite Tubes

Muhammad Fadhil Sahrom,
Muhamad Khairudin Awang,
Mohammad Sukri Mustapa
et al. 2024
ARAM
“…In term of slanted cracks, several works are found such as [9][10][11]. Kuang and Chen [9] used a displacement extrapolation method to investigate the mixed mode crack problems under mode I loading.…”
Section: Introductionmentioning
confidence: 99%
“…They found that their model can be used to predict the stress intensity factors very well. Another study on the slanted crack can be found in [11][12][13]. However, this work focused on the three dimensional cracks.…”
Section: Introductionmentioning
confidence: 99%